Alergie : zapobieganie, jak rozpoznac alergie, najnowsze skuteczne metody leczenia, praktyczne rady dla alergikow i ich rodzin - Mylek, Danuta (Warszawa : W.A.B., 2003)
A popular guide for persons on how to recognize allergies; new efective means of curing them and finally practical help for allergiacs and their families.
Keywords: Allergy -- Popular works